COVID-19 Vaccination Intentions: The Theory of Planned Behavior, Optimistic Bias, and Anticipated Regret - Wolff, Katharina (Frontiers in Psychology, 2021)
The aim of the present study was to investigate intentions to receive a COVID19 vaccine as well as the predictors of such intentions. A representative sample of the Norwegian population (N = 1003) filled in an online questionnaire assessing the components of the Theory of planned behavior (attitudes, subjective norms, and perceived behavioral control), as well as optimistic bias and anticipated regret. Regression analysis showed that a majority of participants intend to get vaccinated. Intentions were predicted by positive attitudes towards vaccination, subjective norms in favor of vaccination in one’s family, perceived behavioral control, and by anticipated regret, explaining 70% of the variance in intentions. Optimistic bias did not predict intentions.